DFT study of CdS-PVA film. Issue 1 (17th February 2015) - Bala, Vaneeta; Tripathi, S K; Kumar, Ranjan
Abstract: Density functional theory has been applied to study cadmium sulphide-polyvinyl alcohol nanocomposite film. Structural models of two isotactic-polyvinyl alcohol (I-PVA) chains around one cadmium sulphide nanoparticle is considered in which each chain consists three monomer units of [-(CH2 CH(OH))-]. All of the hydroxyl groups in I-PVA chains are directed to cadmium sulphide nanoparticle. Electronic and structural properties are investigated using ab-intio density functional code, SIESTA. Structural optimizations are done using local density approximations (LDA). The exchange correlation functional of LDA is parameterized by the Ceperley-Alder (CA) approach. The core electrons are represented by improved Troulier-Martins pseudopotentials. Densities of states clearly show the semiconducting nature of cadmium sulphide polyvinyl alcohol nanocomposite.